SISTEM REKOMENDASI SPESIFIKASI RUMAH LAYAK HUNI BAGI MASYARAKAT PENDATANG BERPENGHASILAN RENDAH MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Risca Setiawan; Iftitaahul Mufarrihah; Anita Andriani; Sri Widoyoningrum (Kampus Akademik Publiser, 2024)
System of Recommendation is a model application of a reliable recommendation, ensuring that recommendations are made in accordance with the buyer's needs and facilitating the buyer's acquisition of a sound opinion on the product being considered for purchase as well as observation of buyer's needs and keadaan. Consumers can use the perumahan recommendation system to find a home in a perumahan area of Lampung without first visiting the home to ask questions. By using the forward chaining method, the perumahan recommendation system will use perumahan data and consumer feedback to suggest or provide recommendations for a home. The forward chaining technique is a writing technique that starts with a fact that is understood, then builds on that fact with the IF and IFTHEN conditional statements. The purpose of this study is to develop a system of recommendations that can identify some criteria for homes that are desired to be matched with the types of homes available in this neighborhood. The results of this study are, unsurprisingly, recommendations for a system that allows consumers to specify criteria that are appropriate to receive results for a home that is in a level or building that is appropriate.